Non-Invasive Brain Stimulation in Neglect Rehabilitation: An Update - Müri, René M.; Cazzoli, Dario; Nef, Tobias; Mosimann, Urs P.; Hopfner, Simone; Nyffeler, Thomas (Frontiers in Human Neuroscience, 2013)
Here, we review the effects of non-invasive brain stimulation (NIBS) such as transcranial magnetic stimulation (TMS) or transcranial direct current stimulation (tDCS) in the rehabilitation of neglect. We found 12 studies including 172 patients (10 TMS studies and 2 tDCS studies) fulfilling our search criteria. Activity of daily living (ADL) measures such as the Barthel Index or more specifically for neglect, the Catherine Bergego Scale were the outcome measure in 3 studies. Five studies were randomized controlled trials with a follow-up time after intervention of up to 6 weeks. One TMS study fulfilled criteria for Class I and one for Class III evidence. The studies are heterogeneous concerning their methodology, outcome measures, and stimulation parameters making firm comparisons and conclusions difficult. Overall, there are however promising results for theta burst stimulation, suggesting that TMS is a powerful add-on therapy in the rehabilitation of neglect patients.